Tannin extraction from mangosteen peel for viscosifier and fluid loss additive in drilling fluid / Nurul Aimi Ghazali … [et al.] - Ghazali, Nurul Aimi; Abd Malek, Mohamad Armanda Alnidzam; Tengku Mohd, Tengku Amran; Alias, Nurhashimah; Rahmat, Norhasyimi (Research Innovation Business Unit, 2014)
The loss of fluids from drilling mud is the most critical parameter that is likely to happen because of unsuccessful filter cake which may cause a wellbore failure if it is not properly controlled. Fluid loss additive being used to control the filtration invasion into the formation. Viscosifier and fluid loss material used to ensure the drilling fluid circulated down the hole in the circulation method of drilling for re-use back. Viscosifier and fluid loss materials are the mud additives that will lessen the amount of drilling fluid disappearing into the formation and to maintain the viscosity of the drilling fluid as low as possible. In this project, extracted tannin from mangosteen peel (ETMP) was used as fluid loss additive. It additionally happens that tannin also can be introduced as a new viscosifier agent for drilling fluid. Fruit peels are one of the sources of powerful antioxidants including mangosteen peel. It is a phenolic antioxidant which contains various bioactive compounds such as phenolic acids, xanthones, anthocyanins as well as tannins. Tannin is a type of biomolecule as opposed to modern synthetic tannin. Tannin also acts as an astringent, bitter plant polyphenolic compound that binds and precipitates proteins and various other organic compound including amino acids and alkaloid. Since tannin is also a polymer it is expected to give some effect on water-based mud (WBM). As the polymer adds as WBM additive, yield stress of the suspensions will decrease and tends to decreases dramatically as the concentration of the polymer increases. This results proved that having polymer as viscosity agent will enhance the viscosity of drilling mud especially WBM. Values of the fluid loss for the free polymer are higher than 15ml which underpass the minimum requirement as suggested by API. But the value will reduce inversely proportional as the concentration of polymer increases. The addition of polymer resulted in increment of apparent viscosity, extensive decrease of the yield stress and in extraordinary diminishment of the fluid loss. Therefore, the characteristics of ETMP were studied to find the effective concentration of ETMP as a viscosifier and fluid loss additive in drilling fluid. The comparison was made on the rheology and filtration properties between basic water based muds (WBM) and experimental WBM. The static fluid loss properties were examined at low temperature and low pressure range of WBM. Low Temperature, Low Pressure (LTLP) Filter Press was used to examine the filtration properties under static condition. Four samples of WBM were prepared prior to the experiments, including basic WBM and WBM with three different additive concentrations. The results indicated that both fluid loss volume and viscosity of experimental WBMs were inversely proportional to the concentration of ETMP added in WBMs. The experiments showed fluid loss volume and viscosity of decreased as the concentration of ETMP increased. Furthermore, the rheology properties of the experimental WBMs including specific gravity, pH value, yield point and gel strength were almost the same with basic WBM which indicate that WBM with extracted tannin applicable for industry use. The application of WBM with extracted tannin as an additive might be used in the formation which happens to have fracture which causes the loss of fluid from drilling fluid. Innovation of ETMP as viscosifier agent and fluid loss additive indicate that WBM can economically enhanced by using biopolymer material.